Pengembangan Produk Olahan Ikan Bandeng untuk Peningkatan Ekonomi Masyarakat Gresik - Dina Amaliyah Mushthoza; Anik Rufaidah; Ririn Rosyidi; Narto; Nailul Izzah (Jurnal Pengabdian Pada Masyarakat, 2022)
DEVELOPMENT OF MİLKFİSH PROCESSED PRODUCTS TO İMPROVE THE GRESİK COMMUNİTY'S ECONOMY. Gresik is one of the districts in East Java Province, with the majority of its coastal communities producing milkfish. As in Tanggulrejo Village, Manyar District is a potential that must be developed, therefore, Lecturer of Industrial Engineering, Qomaruddin Gresik University conducts Community Service as a form of Tridharma of Higher Education. The theme of service is processed milkfish into ice cendol fish milkfish (CEIBAN) with the aim to improve the economy for the people of Tanggulrejo through mothers of PKK Family Welfare Empowerment. The method of service carried out in the form of a workshop on how to make CEIBAN up to the way of packaging so that it can be sold in the market with a large profit. While the results of the workshop received a good reception from the residents of Tanggulrejo, especially the mothers of the pkk local village.